2H‐Chromenes Generated by an Iron(III) Complex‐Catalyzed Allylic Cyclization. Issue 7 (23rd April 2015) - Calmus, L.; Corbu, A.; Cossy, J.
Abstract A straightforward method based on an iron(III) complex‐catalyzed cyclization of 2‐(1‐hydroxyallyl)phenols is reported to access a large variety of 2H‐chromenes. This method was applied to the total synthesis of a natural product, tephrowatsin B.